Alometria reprodutiva de Podocnemis expansa na Área de Proteção Ambiental Meandros do Rio Araguaia, Goiás, Brasil - Ana Paula Gomes Lustosa; José Roberto Ferreira Alves Junior; Anderson Rodrigo da Silva (Multi-Science Journal, 2017)
não há